2015
DOI: 10.1101/gad.256958.114
|View full text |Cite
|
Sign up to set email alerts
|

IncreasedRrm2gene dosage reduces fragile site breakage and prolongs survival of ATR mutant mice

Abstract: In Saccharomyces cerevisiae, absence of the checkpoint kinase Mec1 (ATR) is viable upon mutations that increase the activity of the ribonucleotide reductase (RNR) complex. Whether this pathway is conserved in mammals remains unknown. Here we show that cells from mice carrying extra alleles of the RNR regulatory subunit RRM2 (Rrm2 TG ) present supraphysiological RNR activity and reduced chromosomal breakage at fragile sites. Moreover, increased Rrm2 gene dosage significantly extends the life span of ATR mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 40 publications
5
56
0
Order By: Relevance
“…Through these two distinct effects, ATR promotes the synthesis of dNTPs and limits their consumption in early S phase, thereby suppressing ssDNA accumulation and replication catastrophe. Consistent with our findings, a recent study reported that overexpression of RRM2 suppressed the genomic instability in ATR-deficient mice (Lopez-Contreras et al, 2015). Similar to human ATR, the budding yeast ATR homolog Mec1 also promotes dNTP synthesis and prevents inappropriate firing of dormant origins (Huang and Elledge, 1997; Santocanale et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Through these two distinct effects, ATR promotes the synthesis of dNTPs and limits their consumption in early S phase, thereby suppressing ssDNA accumulation and replication catastrophe. Consistent with our findings, a recent study reported that overexpression of RRM2 suppressed the genomic instability in ATR-deficient mice (Lopez-Contreras et al, 2015). Similar to human ATR, the budding yeast ATR homolog Mec1 also promotes dNTP synthesis and prevents inappropriate firing of dormant origins (Huang and Elledge, 1997; Santocanale et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Second, inactivation of Sml1, an inhibitor of yeast RNR, leads to a ∼2.5-fold increase in dNTP pools (59), and this slight increase is enough to rescue the lethality of the deletion of MEC1 (yeast homolog of mammalian ATR) (59) and to increase the speed of replication forks by approximately 2-fold (60). Third, in mice, increased gene dosage of the small RNR subunit Rrm2 elevates RNR activity, but does not lead to elevated dNTP pools (61), presumably because of the strict allosteric dATP feedback inhibition of the mammalian RNR. Interestingly, despite any detectable increase in dNTP levels, increased gene dosage of the small RNR subunit Rrm2 reduces fragile site breakage and prolongs the survival of ATR mutant mice (61).…”
Section: Discussionmentioning
confidence: 99%
“…Third, in mice, increased gene dosage of the small RNR subunit Rrm2 elevates RNR activity, but does not lead to elevated dNTP pools (61), presumably because of the strict allosteric dATP feedback inhibition of the mammalian RNR. Interestingly, despite any detectable increase in dNTP levels, increased gene dosage of the small RNR subunit Rrm2 reduces fragile site breakage and prolongs the survival of ATR mutant mice (61). Fourth, the deletion of Dun1, a protein kinase that controls yeast RNR, causes a ∼50% reduction of dNTP pools that, in turn, decreases the mutagenic effect of proofreading-deficient Pol e (pol2-4) by approximately threefold and results in a mutation rate comparable to WT levels (18).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic evidence indicates that the essential function of Rad53 and Mec1 is linked to their role at DNA replication forks (Desany et al, 1998). Moreover, the essential function of Rad53 and Mec1 (as well as its counterpart ATR) can be suppressed by elevated levels of dNTPs including deletion of SML1 in yeast cells (Lopez-Contreras et al, 2015; Zhao et al, 1998). All these functions of DNA replication checkpoint kinases in the regulation of firing of late-replication origins, up-regulation of dNTP synthesis and maintenance of replisome functions are conserved in human cells.…”
Section: Introductionmentioning
confidence: 99%